Tibialis Posterior Tenosynovitis as a First Presenting Feature of Pre-clinical Rheumatoid Arthritis: A Case Report and Literature Review - Pokharel, Sabin; Khatri, Arun; Yonjan, Rajendra; Gurung, Yam Prakash (Nepal Orthopaedic Association Journal, 2023)
Tenosynovitis in Preclinical Rheumatoid Arthritis (RA) has been reported. The Tibialis posterior (TP) tendon is the second most commonly affected tendon in the foot and ankle in established RA, but in preclinical RA has not been reported. In this case report, we present a 27 years old lady from Dhading, Nepal, with Preclinical RA with first presentation with Tibialis posterior Tenosynovitis. She was anti-cyclic citrullinated Peptide (CCP) positive but had no arthralgia or morning stiffness. Initial treatment with Non-Steroidal anti-inflammatory drugs failed to alleviate her symptoms. Methotrexate helped improve her symptoms.